Incidence of temporomandibular joint disorders in patients with orofacial deformities - SATO, Shuichi; NAGASAKA, Hiroshi; MITANI, Hideo; SUGAWARA, Junji; MOTEGI, Katsutoshi; KAWAMURA, Hiroshi; GOTO, Satoshi (Journal of the Japanese Society for the Temporomandibular Joint, 1993)
The purpose of this survey was to investigate the prevalence of temporomandibular joint disorder associated with orofacial deformities. The subjects of the epidemiological survey regarding the signs of TMJ disorders (joint noise, joint pain, masticatory muscles pain and jaw movement) were 172 untreated patients with orofacial deformities, who visited Oral and Maxillofacial Surgery I of Tohoku University from 1989 to 1992. The results were as follows: 1. Some symptoms of TMJ disorders were found in 53.5% of the total. No significant difference was found between males and females in the incidence of disorder. 2. Joint noise was found in 38.3%, joint pain in 9.3%, masticatory pain in 7.0% and disturbance of jaw movement in 2.3% of the subjects. 3. The incidence of TMJ disorders was 37.5% in patients under 14 years old and increased with age. It was 77.7% in patients over 30 years old. 4. The patients of skeletal Class I (p<0.01) and ClassII (p<0.05) showed higher incidence of TMJ disorders than ClassIII.